O EFEITO DA ESPLENECTOMIA SOBRE A OBESIDADE INDUZIDA POR GLUTAMATO MONOSSÓDICO(MSG) - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
Introduction: Adipose tissue excess is associated to the metabolic syndrome (MS), resulting in several physiological changes, such as, glucose intolerance, dyslipidemia, hypertension and insulin resistance, a set of symptoms intimately linked to the development of type II Diabetes Mellitus (DM2). Obese and/or diabetic people also present a low degree of chronic inflammation intertwining the different MS clinical and physiopathological symptoms. Recently, the spleen, one of the main lymphoid organs in our body, has been appointed as the active organ in the obesity inflammatory process. Objective: This study investigated the effects of spleenectomy in SM induced through the neonatal treatment with monosodium glutamate (MSG). Methodology: Wistar male rats received MSG injections (4g/kg) from the first to the fifth day of life, while de control group (CON) received equimolar saline. The animals were weaned on the 21st day and on day 60 half of the animals were submitted to spleenectomy (ESPL) and the spleen was removed. Four experimental groups were formed. CON-NO (not operated); CON-ESPL; MSG-NO; MSG-ESPL. From day 21 to day 90, food and water consumption as well as body weight were evaluated. On day 90, pancreatic islets were isolated using the collagenase technique and incubated in glucose (5,6; 8,3; and 16,7mM) or glucose (11.1 mM) plus L-NAME (2,5; 5,0 and 10,0nM) inhibitor of the nitric oxide producing enzyme (iNOS). The insulin was dosed through radioimmunoassay. Blood was collected and plasma separated for glucose, triglycerides and total cholesterol biochemical dosages. Insulin resistance was evaluated using the insulin tolerance test (1U/Kg). Hemogram automated analysis was also carried out. White and brown fat depots, as well as pancreas and spleen were removed for histological procedures. Data was expressed as mean ± standard error of the mean (sem). Variance analysis (ANOVA), with Bonferroni post-test (p<0,05) were employed. Results and Discussion: Rats MSG-NO presented insulin resistance, increase of about 78% in the insulin, triglycerides and cholesterol levels. Additionally, the content of body fat was around 215% higher in this group in relation to the CON-NO rats, without changing the food control. The size of adipocytes and pancreatic islets was around 58% smaller in this group when compared to CON-NO rats. Pancreatic islets of MSG-NO rats presented insulin hypersecretion, followed by alterations in the response to the iNOS blocker. The hematocrit and number of leucocytes was around 50% higher in MSG-NO rats when compared to the CON-NO group. The ESPL abolished hyperinsulinaemia, insulin resistance and reduced the food ingestion in MSG rats. However, ESPL elevated approximately 21% the level of triglycerides and cholesterol in the MSG-ESPL. MSG-ESPL rats presented alteration in the lymphocyte and granulocyte profile after surgery. The ESPL reduced approximately 25% and 63%, respectively, the hypertrophy of adypocites and pancreatic islets in MSG rats, as well as normalized the insulin hypersecretion. Finally, SPL normalized the response to the iNOS blocker. Conclusions: Spleenectomy reduces obesity, hyperinsulinaemia and resistance to insulin in MSG rats, such alterations might be related to reduction in the inflammatory process originated in the spleen.
Keywords: Baço; inflamação; Ilhotas; Spleen; inflammation; islets; CNPQ::CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR